2014
DOI: 10.1002/jib.180
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of volatile and non-volatile fractions of selected traditionally brewed Korean rice wines

Abstract: *Antioxidant activities of traditionally brewed Korean rice wines have recently been reported. The objective of this study was to identify the antioxidant activities of the volatile and non-volatile fractions of three Korean rice wines, and further to identify the active ingredients responsible for the antioxidant properties. Volatile and non-volatile components of three rice wines, Measilju, Kukwhaju and Gugijaju, were separated into seven fractions according to their polarities. Antioxidant activities were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The application of headspace solid-phase microextraction (HS-SPME) has been increasing in food analysis because this method allows the provision of more realistic knowledge of the volatile fraction of a particular food and its contribution to aroma [21,22]. Here, HS-SPME combined with GC TOF-MS, which offers very fast spectral acquisition rates and allows the separation of a substantial number of compounds, was applied for the determination of the characteristic volatile profiles of Xanthii Fructus because flavor could be an important phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The application of headspace solid-phase microextraction (HS-SPME) has been increasing in food analysis because this method allows the provision of more realistic knowledge of the volatile fraction of a particular food and its contribution to aroma [21,22]. Here, HS-SPME combined with GC TOF-MS, which offers very fast spectral acquisition rates and allows the separation of a substantial number of compounds, was applied for the determination of the characteristic volatile profiles of Xanthii Fructus because flavor could be an important phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…This assay demonstrates the long‐term antioxidative activity of a chemical 16 . Moreover, it was mainly used to analyze the antioxidative activity of natural volatile extracts 13,14,19 . Figure 3 shows the antioxidative activity of each fraction obtained from the volatile extract, which was examined by aldehyde/carboxylic acid assay; this assay measured the remaining hexanal content after 30 days of reaction with test solution.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, ester was the flavour compounds. However, various studies have reported International Journal of Food Science and Technology 2022 that the main volatile compounds in rice are aldehydes, ketones, furans, phenol derivatives, terpenes, linear hydrocarbons and esters (Jeong et al, 2011;Zeng et al, 2012;Lyu et al, 2013;Kim et al, 2014;Lipan et al, 2016). In addition, previous research has investigated the volatile compounds in samples of cooked rice from six cultivars obtained using dynamic headspace sampling.…”
Section: Volatile Compounds Extracted From Ricementioning
confidence: 99%